Liver Necrosis and Hemorrhage due to Gastroduodenal Artery Pseudoaneurysm after total Pancreatectomy. Report of a case - Kurşat Rahmi Serin; Muharrem Oner; Nadir Adnan Hacım (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Although mortality after pancreatectomy in high-volume centers is less than 3%, morbidity is still as high as 18-52%. Postpancreatectomy vasculary complication is less frequent but much mortal than anastomotic problems. Postpancreatectomy vasculary complication is a life-threatening entity and it must be managed urgently. Here we report a case treated with emergent laparotomy for delayed liver ischemia and massive bleeding after total pancreatectomy. Patient was discharged without any complication at the 3rd week of emergent laparotomy for aneurismatic hemorrhage. Upper gastrointestinal bleeding in the late postoperative period following pancreatoduodenectomy should alert the surgeon to the possibility of a ruptured visceral vasculary pseudoaneurysm.